2022
DOI: 10.1155/2022/9616582
|View full text |Cite|
|
Sign up to set email alerts
|

High-Throughput Sequencing Investigation of Bacterial Diversity in Chronic Suppurative Otitis Media and Middle Ear Cholesteatoma

Abstract: Background. Chronic otitis media is a common middle ear disease in otolaryngology. Bacterial infection is considered as the cause of the disease, but relying on conventional bacterial cultures can be problematic for identifying specific pathogens. Current research suggests that bacteria in microbial communities can only be identified by rDNA sequencing of bacteria. Methods. This cross-sectional study utilized broad-range PCR amplification of 16S rRNA genes with clone analysis to compare bacterial diversity in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%